2015
DOI: 10.18805/lr.v38i5.5947
|View full text |Cite
|
Sign up to set email alerts
|

Field resistance of pigeonpea [<italic>Cajanus cajan</italic> (L.)] germplasm lines to <italic>Fusarium</italic> wilt disease in India

Abstract: A study was conducted at Badnapur in the district of Jalna on the behavior of two hundred and forty-eight pigeonpea germplasm lines representing different levels of resistance to pigeonpea wilt disease. Out of 248 germplasm lines Resistant (R), Moderately Resistant (MR), Moderately Susceptible (MS), Susceptible (S), Highly Susceptible (HS) and Very Highly Susceptible (VHS) reaction was given by 2, 8, 10, 25, 131 and 72 entries, respectively. Germplasm lines GL<sub>4</sub> (7088) and GL<sub>90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Fig. 5 indicated that the similar results of 100 seed weight was observed by Tej et al, (2003), Pawar et al, (2015), Vijay Bhaskar, (2016), Parameshwarappa, (2002) and Akaazua et al, (2017). Seed yield q/ha was found to be significantly higher in G-13 (24.90 q.)…”
Section: S415supporting
confidence: 87%
See 2 more Smart Citations
“…Fig. 5 indicated that the similar results of 100 seed weight was observed by Tej et al, (2003), Pawar et al, (2015), Vijay Bhaskar, (2016), Parameshwarappa, (2002) and Akaazua et al, (2017). Seed yield q/ha was found to be significantly higher in G-13 (24.90 q.)…”
Section: S415supporting
confidence: 87%
“…Fig. 1 indicated that the similar results of Field emergence percentage was observed by Mohar et al, (2014); Varshney et al, (2010); Pawar et al, (2015); Egbe and Venge, (2008); Rani et al, (2015) and Upadhyaya et al, (2011).…”
Section: S413supporting
confidence: 86%
See 1 more Smart Citation
“…Jaggal, et al, (2014) observed that 39 accessions were resistant to wilt disease. Pawar, et al., (2015) reported that two germplasm lines viz., ICP-7088 and ICP-8863 were only wilt resistant.…”
Section: Percent Disease Incidence (Pdi) = [Number Of Plants Wilted /mentioning
confidence: 99%